PENGARUH SALES GROWTH, CORPORATE GROWTH, DAN RETURN ON EQUITY (ROE) TERHADAP NILAI PERUSAHAAN - Eva Maulia Mutvi Widodo; Eko Widodo; Kukuh Harianto (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to determine the effect of sales growth, corporate growth, and return on equity on the value of companies in the mining industry sector listed on the Indonesia Stock Exchange for the period of 2021. The type of this research is quantitative. The data used is secondary data. The sample selection used the purposive sampling method, from 42 mining sector companies listed on the Indonesia Stock Exchange, 30 company samples were obtained. The research method used in this study is multiple linear regression analysis using the Eviews10 program. The results of this study indicate that the sales growth variable has a negative and insignificant effect on the company's value (PBV). The corporate growth variable has a negative and significant effect on the company's value (PBV). Meanwhile, the return on equity (ROE) variable has a positive and significant effect on the company's value. (PBV). The value of the regression coefficient shows that the independent variables can explain the dependent variable by 46%, while the remaining 54% is explained by other variables outside this study.